Lethality econometric model validity for COVID-19 infected pleople, Peru May 2020 - Flores Arocutipa, Javier Pedro (2020)
Objective: To prove through an econometric model the number of deaths in Peru is significantly related to the number of infected cases of COVID-19. Method: Basic research, not experimental. For the whole country of Peru, 52 series (days) have been taken and in the specific case from the department of Moquegua, 37 series in the period from March 16 until May 10, 2020. The database of the Ministry of Health has been used, the COVID-19 Situation Chamber and the Moquegua Regional Health Management; Pearson's R and R2 are used. Regression models were generated on May 10 (after 52 days after the first death), which must be contrasted on May 31. Results: The models comply with the prediction, with a high and significant R2 and Rho. Conclusions: The death prediction models are corroborated as of May 31, 73 days after the first death in Peru. Pearson's correlation and determination levels in countries which are coming up from the COVID-19 emergency, regions throughout Peru have a high and significant relationship between infected and deceased. The bigger number of infected, the bigger number of deaths. In number and proportion are adults and older adults. 72.5% are male. In Moquegua it is shown the relationship between the levels of diagnostic tests performed and infected.